Detection of mycotoxygenic mold and identification of lead and mercury in maca flour (Lipidium meyenii Walp.) - Solano-Medina, Nansi Marsela (2021)
Maca (Lipidium meyenii Walp,) is a Peruvian product with different properties and health benefits, however, depending on its nature both in its processed state and as a raw material, it can present polluting substances from its natural appearance or state of conservation. The objective of the study was to detect mycotoxigenic molds and identify heavy metals of lead and mercury in maca flour from the Buenos Aires agricultural market in the Carhuamayo District, Huancayo Province and Junín Department. The detection of molds was made by the direct method, appreciating species of the genus Cephalosporium sp. (HMD1) and Penicillium sp. (HMD2) and by the indirect method a dilution (-7) 5x108 cfu / mL of yeast was obtained. In the identification of heavy metals by atomic absorption spectrophotometry, the presence of lead was evidenced in 0.17 mg / kg average amount at the toxic value of the permissible limit and mercury in concentrations lower than the detection limit of the equipment of 1 ppm.